The difference in the level of altruism between cyberspace and real life - Granda, Konrad (My University, 2012)
This research was conducted for four reasons. The first one was to examine the differences between altruism in the cyberspace and real life. The results regarding altruism in the cyberspace were viewed from the perspective of Klisanin’s theory of Digital Altruism (Klisanin, 2011). Second reason was to examine the relationship between interpersonal trust and knowledge sharing in the Internet environment and make a comparison with its ‘real life’ counterpart. In the third step relationship between interpersonal trust and social identification was tested, data from the two dimensions were compared. Finally, social identity’s relations with knowledge sharing were examined in regard to cyberspace and ‘real life’. In this research, 271 participants from three universities completed two opened-ended questions regarding altruism in ‘real life’ and ‘cyberspace’ and three questionnaires. Interpersonal Trust Scale by Julian Rotter (1991), Aspects of Identity Questionnaire (AIQ IV) by Jonathan Cheek (2002) and Questionnaire on Knowledge Sharing Behavior by Nor Intan Saniah binti Sulaiman (2010). Regression analysis showed that trust has strong impact on community factor of knowledge sharing and on social identification in both cyberspace and ‘real life’. The study also showed that social identification strongly influences personal and community factors of knowledge sharing in cyberspace environment and only community factor in ‘real life’. Altruistic activities are directed to people familiar to the altruist. Cyberspace altruistic activities are connected with Klisanin’s everyday and creative digital altruism.

Badanie to zostało przeprowadzone z czterech powodów. Pierwszym było zbadanie różnic pomiędzy altruizmem w cyberprzestrzeni i świecie rzeczywistym. Altruizm w cyberprzestrzeni został porównany z teorią altruizmu cyfrowego Klisanin (2011). Drugim powodem było zbadanie związku między zaufaniem interpersonalnym a dzieleniem się wiedzą w środowisku Internetu i porównanie go z odpowiednikiem ze świata rzeczywistego. W trzecim kroku została zbadana relacja zaufaniem interpersonalnym a identyfikacją społeczną, dane z obydwu wymiarów zostały porównane. Wreszcie, związek identyfikacji społecznej z dzieleniem się wiedzą został zbadany w odniesieniu do cyberprzestrzeni i świata rzeczywistego. W badaniu wzięło udział 271 uczestników z trzech uczelni, którzy mieli odpowiedzieć na dwa pytania dotyczące altruizmu w świecie rzeczywistym i cyberprzestrzeni oraz trzy kwestionariusze: Skalę Interpersonalnego Zaufania autorstwa Juliana Rottera (1991), Kwestionariusz Aspektów Identyfikacji (AIQ IV) autorstwa Jonathana Cheeka (2002) oraz Kwestionariusz Zachowań Dzielenia się Wiedzą autorstwa Nor Intan Saniah binti Sulaiman (2010). Analiza regresji wykazała, że zaufanie ma silny wpływ na społeczny czynnik dzielenia się wiedzą oraz identyfikację społeczną, zarówno w cyberprzestrzeni jak i świecie rzeczywistym. Badanie wykazało również, że identyfikacja społeczna silnie wpływa na personalny oraz społeczny czynnik dzielenia się wiedzą w środowisku cyberprzestrzeni i tylko na czynnik społeczny w świecie rzeczywistym. Altruistyczne działania skierowane są na ludzi, którzy są znani altruiście. Działania altruistyczne w cyberprzestrzeni powiązane są z codziennym oraz kreatywnym cyfrowym altruizmem Klisanin.
Różnica w poziomie altruizmu w cyberprzestrzeni i świecie rzeczywistym
Keywords: altruism in the cyberspace; real life; of Klisanin’s theory; internet